Qualitatively capturing institutional logics. (November 2016) - Reay, Trish; Jones, Candace
There is an ever-increasing volume of studies investigating institutional logics, and yet qualitative methods for studying this phenomenon are not clear. In this essay, we examine how qualitative scholars convince their readers that they are actually studying institutional logics. We identify three different, but non-exclusive techniques that have been employed: pattern deducing, pattern matching, and pattern inducing. For each of these approaches, we explain the ontological assumptions, methodological techniques, challenges, and benefits. In addition, we provide examples of how specific studies have analyzed and presented qualitative data to improve theory about institutional logics.